A Horizontally Scalable WebSocket Architecture for Cost-Effective Online Examination Proctoring System on AWS Cloud Infrastructure - Nugroho, Eko Cahyo (Engineering, MAthematics and Computer Science Journal (EMACS), 2025)
In this research work we present the cost-effective prototype of a WebSocket server with a horizontal scaling feature on AWS Cloud Service. AWS API Gateway for establishing WebSocket connections also works but is exceedingly expensive for schools. The solution presented in this study proposes an on-premise WebSocket server deployed at AWS EC2 instances. The server utilizes Node. js's cluster module to make the most out of the CPU's cores and has also implemented a Redis pub/sub mechanism to easily horizontal scale it to many EC2 instances. The system architecture utilizes DynamoDB to store students' proctoring status recorded on the first attempt at the quiz. Then, the real status update is delivered by WebSocket message. The implementation shows effective real-time monitoring capabilities for online examinations, including student activity tracking, automated disconnection detection, and proctor-student interaction features. The results show improved cost efficiency compared to API Gateway as the WebSocket server. This solution provides schools with a cost-effective and reliable proctoring feature in LMS for implementing online examination proctoring systems at scale.